Development of basic pencak silat e-book teaching materials based on OBE - Sinulingga, Albadi; Kasih, Indra; Simatupang, Nurhayati; Silaen, Suandi; Budiman, Ali (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
The study presented the development of an Outcome-Based Education (OBE)-based pencak silat e-book as a learning media for coaching education students. The materials included a discussion on the history of pencak silat, followed by core content on basic pencak silat techniques, starting from basic stances, hand attacks, blocks, dodges, kicks, catches, sweeps and takedowns, falls, to step patterns, all explained in detail based on OBE principles. The population of this study was students of the 2022 cohort who took the pencak silat course at Universitas Negeri Medan, totaling 93 students. This study employed the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. Data were collected using questionnaires and documentation. The small-group test results showed a percentage value of 87% with a very good category. The large-group test results showed an average overall assessment score of 86%, also in the very good category. The research results obtained show that the OBE-based e-book teaching media for pencak silat courses that was developed is suitable for use as a teaching medium.